Porti e Approdi Fluviali in Italia Peninsulare - Luciano, Alessandro (Archaeopress, 2019)
This book analyses the Roman and early medieval ports of Italy and the building techniques used in their structures; it displays the elements of continuity and discontinuity revealed during these centuries.